The terms used by al-Khalil ibn Ahmad on the description of the Arab. (Journal of Oriental Studies, 2016)
This article discusses the terms used by al-Khalil Ibn Ahmad the Arab sounds on the description, as well as reveals their values.
Keywords: a vowel; consonant; the labial sound; majhur; mahmus